1996
DOI: 10.1152/ajpendo.1996.270.3.e400
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of canine gracilis muscle during contraction with partial ischemia

Abstract: The metabolic effects of partial ischemia on canine skeletal muscle were examined during 20 min of isometric contraction. A reduction in blood flow of approximately 75% resulted in an approximate 40% reduction in contractile function. Muscle lactate accumulation and phosphocreatine (PCr) hydrolysis were greater during ischemia, indicating a greater reliance on anaerobic ATP regeneration. Pyruvate dehydrogenase transformation to its active form (PDCa) during contraction was not affected by ischemia, such that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
41
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 25 publications
8
41
4
Order By: Relevance
“…A recent series of studies by our group has demonstrated the existence of metabolic inertia at the onset of contraction (27,28,(33)(34)(35)(36). On the basis of evidence from these studies, we believe that the delay in acetyl-CoA provision at the onset of exercise, which we have termed the "acetyl group deficit" (27), is a principal determinant of the oxygen deficit (27,33,34).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A recent series of studies by our group has demonstrated the existence of metabolic inertia at the onset of contraction (27,28,(33)(34)(35)(36). On the basis of evidence from these studies, we believe that the delay in acetyl-CoA provision at the onset of exercise, which we have termed the "acetyl group deficit" (27), is a principal determinant of the oxygen deficit (27,33,34).…”
mentioning
confidence: 89%
“…We have demonstrated that pretreatment of canine skeletal muscle with sodium dichloroacetate, an inhibitor of pyruvate dehydrogenase kinase (32), near maximally activated the PDC and acetylated muscular carnitine and free CoASH pools at rest (27,34,35,36). During subsequent submaximal ischemic contraction (blood flow and, hence, oxygen availability held at its resting state), dichloroacetate overcame the acetyl group deficit, reduced ATP resynthesis from oxygen-independent routes, and improved the maintenance of contractile function over the course of contraction compared with control (27,34,35,36).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Timmons et al (28,30) have recently demonstrated that activating the PDC before the initiation of an ischemic contractile period resulted in less depletion of muscle PCr and ATP, lower lactate accumulation, and enhanced subsequent force production compared with the control ischemic situation with no PDC activation. This indicates that when partial ischemia was imposed on contracting muscle at the onset of contractions, substrate availability for oxidative phosphorylation was inadequate and the reduced O 2 availability was not the only factor determining subsequent muscle performance.…”
Section: Skeletal Muscle Bioenergetics After Blood Flow Reductionmentioning
confidence: 99%
“…Timmons et al (28)(29)(30) recently demonstrated that substrate availability through the pyruvate dehydrogenase complex (PDC) for carbohydrate oxidation in the tricarboxylic cycle can affect subsequent muscle performance during moderate ischemia. These investigators (30) demonstrated that having the PDC enzyme fully activated at the onset of an ischemic contractile period resulted in significantly less PCr hydrolysis and lactate accumulation and subsequently less fatigue compared with the same ischemic blood flow reduction with PDC starting from the normal resting deactivated state.…”
mentioning
confidence: 99%